Pengaruh Lingkungan Kerja dan Motivasi terhadap Perkembangan Karir Karyawan - Arisman Zebua; Apriyanti Apriyanti (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to analyze the influence of work environment and motivation on employee career development. A conducive work environment and strong motivation are considered important factors in encouraging employees to develop their skills and competencies, which ultimately contribute to career advancement. The research method used was a quantitative survey with sampling from employees of various companies. Data was collected through a questionnaire containing questions regarding employees' perceptions of the work environment, motivation levels, as well as their career progression. The regression analysis results show that a supportive work environment significantly enhances employees' career progression, while intrinsic motivation also plays an important role in accelerating career advancement. The implications of this study suggest that companies should pay attention to the quality of the work environment and provide the right motivational boost to optimize employees' career development.